Factors Associated with Discharge to a Skilled Nursing Facility after Transcatheter Aortic Valve Replacement Surgery - Horne, Carolyn E.; Goda, Tamara S.; Nifong, L. Wiley; Kypson, Alan P.; O’Neal, Wesley T.; Kindell, Linda C.; Jindal, Charulata; Efird, Jimmy T. (My University, 2018)
An assumption regarding transcatheter aortic valve replacement (TAVR), a minimally invasive procedure for treating aortic stenosis, is that patients remain at, or near baseline and soon return to their presurgical home to resume activities of daily living. However, this does not consistently occur. The purpose of this study was to identify preoperative factors that optimally predict discharge to a skilled nursing facility (SNF) after TAVR. Delineation of these conditions is an important step in developing a risk stratification model to assist in making informed decisions. Data was extracted from the American College of Cardiology (ACC) transcatheter valve therapy (TVT) registry and the Society of Thoracic Surgeons (STS) database on 285 patients discharged from 2012–2017 at a tertiary referral heart institute located in the southeastern region of the United States. An analysis of assessment, clinical and demographic variables was used to estimate relative risk (RR) of discharge to a SNF. The majority of participants were female (55%) and white (84%), with a median age of 82 years (interquartile range = 9). Approximately 27% (n = 77) were discharged to a SNF. Age > 75 years (RR = 2.3, p = 0.0026), female (RR = 1.6, p = 0.019), 5-meter walk test (5MWT) >7 s (RR = 2.0, p = 0.0002) and not using home oxygen (RR = 2.9, p = 0.0084) were identified as independent predictive factors for discharge to a SNF. We report a parsimonious risk-stratification model that estimates the probability of being discharged to a SNF following TAVR. Our findings will facilitate making informed treatment decisions regarding this older patient population.
Keywords: aortic stenosis, risk stratification, skilled nursing facility, transcatheter aortic valve replacement